2012
DOI: 10.1038/nrmicro2875
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Hsp90: a biological transistor that tunes cellular outputs to thermal inputs

Abstract: Preface Hsp90 is an essential, abundant, and ubiquitous eukaryotic chaperone that has crucial roles in protein folding and modulates the activities of key regulators. The fungal Hsp90 interactome, which includes numerous client proteins such as receptors, protein kinases and transcription factors, displays a surprisingly high degree of plasticity that depends on environmental conditions. Furthermore, although Hsp90 levels increase following environmental challenges, Hsp90 activity is tightly controlled via pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
97
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 142 publications
(255 reference statements)
3
97
2
10
Order By: Relevance
“…HSP90 transcription is activated by Hsf1, which is negatively regulated by interaction with Hsp90 as an autoregulatory loop (Leach et al 2012). Interestingly, HSP90 expression was rapidly induced in both WT and sch9D strains by temperature upshift, which is in stark contrast to HSF1 expression patterns ( Figure 4E and Figure S5).…”
Section: Resultscontrasting
confidence: 39%
See 2 more Smart Citations
“…HSP90 transcription is activated by Hsf1, which is negatively regulated by interaction with Hsp90 as an autoregulatory loop (Leach et al 2012). Interestingly, HSP90 expression was rapidly induced in both WT and sch9D strains by temperature upshift, which is in stark contrast to HSF1 expression patterns ( Figure 4E and Figure S5).…”
Section: Resultscontrasting
confidence: 39%
“…and also serves as a key negative feedback regulator of Hsf1 in most fungi (Leach et al 2012). In our study, we also found that HSP90 expression was strongly induced upon temperature upshift.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…How Hsp90 deals with different kinds of environmental stresses is well documented (23,28). Yet, few studies have examined its role in carbon source metabolism.…”
mentioning
confidence: 99%
“…By associating with different cochaperones and cofactors, Hsp90 helps a wide range of client proteins involved in various biological processes (19,(23)(24)(25). For instance, with the cooperation of the Hsp70 and Hsp40 cochaperones, Hsp90 binds to the glucocorticoid receptor to maintain it in a conformation required for steroid hormone binding (26).…”
mentioning
confidence: 99%